The Reshaping and Effect Evaluation of Immersive Communication on Museum Cultural Experience - Huang Gang; Zhong Junjie (SHS Web of Conferences)
This article explores the reshaping of museum cultural experience through immersive communication and its effectiveness evaluation. With the development of digital technology, immersive communication technologies such as virtual reality, augmented reality, etc. have gradually become important tools for innovative exhibitions and educational models in museums. Through multi-sensory interactive experiences, immersive communication not only breaks the spatial and exhibit limitations of traditional museums, but also enhances audience participation and emotional resonance, promoting the depth and breadth of cultural experiences. The article first introduces the concept of immersive communication technology and its application in museums and analyzes its advantages and potential in cultural communication. Furthermore, the limitations of traditional museum cultural experiences were discussed, and how immersive communication reshapes museum cultural experiences in terms of interactivity, immersion, and cultural understanding were elaborated. Finally, based on an immersive exhibition case at a certain museum, this article evaluates the effectiveness of immersive communication in enhancing cultural learning, emotional identification, and audience satisfaction. Research has shown that immersive communication technology significantly improves the audience’s knowledge acquisition, emotional identification, and cultural identity, while enhancing the interactivity and attractiveness of exhibitions. In summary, immersive communication technology has brought revolutionary changes to the cultural experience of museums and is of great significance in enhancing the educational function and cultural dissemination effect of museums.